Nature's noblemen : transatlantic masculinities and the nineteenth-century American West - Rico, Monica, 1971- (Lamar series in western history., 2013)
Monica Rico explores the myth of the American West in the 19th century as a place for men to assert their masculinity by 'roughing it' in the wilderness and reveals how this myth played out in a transatlantic context. She uncovers the networks of elite men - British and American - who circulated between the West and the metropoles of London and New York.